Comparison of analgesic efficacy of transversus abdominis plane block with direct infiltration of local anesthetic into surgical incision in lower abdominal gynecological surgeries - Vijayalakshmi Sivapurapu; Arumugam Vasudevan; Sumanlata Gupta; Ashok S Badhe (Wolters Kluwer Medknow Publications, 2013)
Background: Transversus abdominis plane block is a safe, simple and effective technique of providing analgesia for lower abdominal surgeries with easily identifiable landmarks. Aims: To compare the analgesic efficacy of transversus abdominis plane block with that of direct infiltration of local anesthetic into surgical incision in lower abdominal procedures. Settings and Design: Prospective randomized controlled trial in lower abdominal surgeries done under general anesthesia. Materials and Methods: 52 ASA I-II patients undergoing lower abdominal gynecological procedures under general anesthesia were divided randomly into two groups each after written informed consent. A bilateral TAP block was performed on Group T with 0.25% bupivacaine 0.6 ml/kg with half the volume on either side intra-operatively after skin closure before extubation using a short bevelled needle, whereas Group I received local infiltration intra-operatively after skin closure with the same amount of drug. The time taken for the first rescue analgesic and visual analog score (VAS) was noted, following which, the patient was administered intravenous morphine 0.1 mg/kg and connected to an intravenous patient controlled analgesia system with morphine for 24 hrs from the time of block administration. 24 h morphine requirement was noted. VAS and sedation scores were noted at 2, 4, 6 and 24 h postoperatively. Statistical Analysis Used: The results were analyzed with SPSS 16. A P value < 0.05 was considered significant. Duration of analgesia and 24 h morphine requirement was analysed by Student's t-test. VAS scores, with paired comparisons at each time interval, were performed using the t-test or Mann-Whitney U-test, as appropriate. Categorical data were analyzed using Chi square or Fisher's exact test. Results: In Group T, the time to rescue analgesic was significantly more and the VAS scores were lower ( P = 0.001 and 0.003 respectively). The 24 hr morphine requirement and VAS at 2, 4, 6 and 24 h were less in the Group T ( P = 0.001). Incidence of PONV was significant in Group I ( P = 0.043), whereas Group T were less sedated at 2 and 4 h ( P = 0.001 and 0.014). Conclusions: Transversus abdominis plane block proved to be an effective means of analgesia for lower abdominal surgeries with minimal side-effects.